Real-world SARS CoV-2 testing in Northern England during the first wave of the COVID-19 pandemic. Issue 1 (July 2021) - Farooq, Hamzah Z.; Davies, Emma; Brown, Benjamin; Whitfield, Thomas; Tilston, Peter; McEwan, Ashley; Birtles, Andrew; O'Hara, Robert; Spencer, Hannah; Hesketh, Louise; Ahmad, Shazaad; Guiver, Malcolm; et al.
Highlights: Nasal swabs are the optimum samples for diagnosing SARS-CoV-2 via PCR in this dataset. None of the faecal, fluid or CSF samples were positive for SARS-CoV-2. Highest assay positivity was shown by the dual-target Roche assay. Multiple platforms and assays are required for rapid mass-testing in pandemics. Abstract: Objectives: SARS-CoV-2 emerged in South Asia in 2019 and has resulted in a global pandemic. Public Health England (PHE) Manchester rapidly escalated testing for SARS-CoV-2 in the highest COVID-19 incidence location in England. The results of the PHE Manchester SARS-CoV-2 surveillance during the first wave are presented. Methods: Retrospective data were collected for patients fitting the PHE SARS-CoV-2 case definition from 11th February to 31st August 2020. Respiratory tract, tissue, faecal, fluid and cerebrospinal (CSF) samples were tested for SARS-CoV-2 by a semi-quantitative real-time reverse-transcription PCR. Results: Of the 204, 083 tests for SARS-CoV-2, 18, 011 were positive demonstrating a positivity of 8.90%. Highest positivity was in nasal swabs (20.99%) followed by broncheo-alveolar lavage samples (12.50%). None of the faecal, fluid or CSF samples received were positive for SARS-CoV-2. Conclusions: There was a high incidence of SARS-CoV-2 patients in the North-West of England during the first UK wave of the Covid-19 pandemic. Highest positivity rate was in nasal specimens suggesting this is the optimum sample type within this dataset for detecting SARS-CoV-2. Further studies are warranted to assess the utility of testing faecal, fluid and CSF samples. Rapid escalation of testing via multiple platforms was required to ensure prompt diagnosis and isolate infected cases to reduce transmission of the virus.